2018
DOI: 10.1101/301150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Searching Algorithm for Type IV Effector proteins (S4TE) 2.0: improved tools for type IV effector prediction, analysis and comparison

Abstract: Bacterial pathogens have evolved numerous strategies to corrupt, hijack or mimic cellular processes in order to survive and proliferate. Among those strategies, Type IV effectors (T4Es) are proteins secreted by pathogenic bacteria to manipulate host cell processes during infection. They are delivered into eukaryotic cells in an ATP-dependent manner via the type IV secretion system, a specialized multiprotein complex. T4Es contain a wide spectrum of features including eukaryotic-like domains, localization signa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Bioinformatics analysis using the prediction software S4TE2 (36) indicated that CstK harbors features corresponding to secreted effector proteins, including a promoter motif typically found in effector proteins from intra-vacuolar bacterial pathogens and a putative C-terminal E-block domain (37), suggesting that CstK is indeed a Coxiella effector protein ( Fig. 1A).…”
Section: Cstk Is a Dot/icm Effector Proteinmentioning
confidence: 99%
“…Bioinformatics analysis using the prediction software S4TE2 (36) indicated that CstK harbors features corresponding to secreted effector proteins, including a promoter motif typically found in effector proteins from intra-vacuolar bacterial pathogens and a putative C-terminal E-block domain (37), suggesting that CstK is indeed a Coxiella effector protein ( Fig. 1A).…”
Section: Cstk Is a Dot/icm Effector Proteinmentioning
confidence: 99%